Validity and reliability of the Persian version of the Brief Aging Perceptions Questionnaire in Iranian older adults - Sadegh Moghadam L (Dove Medical Press, 2016)
Leila Sadegh Moghadam,1,2 Mahshid Foroughan,1,3 Farahnaz Mohammadi Shahboulaghi,1,4 Fazlollah Ahmadi,5 Moosa Sajjadi,6 Akram Farhadi3 1Iranian Research Center on Aging, University of Social Welfare and Rehabilitation Sciences, Tehran, Iran; 2Nursing Department, Gonabad University of Medical Sciences, Gonabad, Iran; 3Department of Ageing, University of Social Welfare and Rehabilitation, Tehran, Iran; 4Nursing Department, University of Social Welfare and Rehabilitation Sciences, Tehran, Iran; 5Nursing Department, Faculty of Medical Sciences, Tarbiat Modares University, Tehran, Iran; 6Department of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Gonabad University of Medical Sciences, Gonabad, Iran Background: Perceptions of aging refer to individuals’ understanding of aging within their sociocultural context. Proper measurement of this concept in various societies requires accurate tools. Objective: The present study was conducted with the aim to translate and validate the Brief Aging Perceptions Questionnaire (B-APQ) and assess its psychometric features in Iranian older adults. Method: In this study, the Persian version of B-APQ was validated for 400 older adults. This questionnaire was translated into Persian according to the Wild et al’s model. The Persian version was validated using content, face, and construct (using confirmatory factor analysis) validities, and then its internal consistency and test–retest reliability were measured. Data were analyzed using the statistical software programs SPSS 18 and EQS-6.1. Results: The confirmatory factor analysis confirmed construct validity and five subscales of B-APQ. Test–retest reliability with 3-week interval produced r=0.94. Cronbach’s alpha was found to be 0.75 for the whole questionnaire, and from 0.53 to 0.77 for the five factors. Conclusion: The Persian version of B-APQ showed favorable validity and reliability, and thus it can be used for measuring different dimensions of perceptions of aging in Iranian older adults. Keywords: Brief Aging Perception Questionnaire, psychometric study, older adults, validity